Candidate photoferroic absorber materials for thin-film solar cells from naturally occurring minerals: enargite, stephanite, and bournonite - Wallace, Suzanne K.; Svane, Katrine L.; Huhn, William P.; Zhu, Tong; Mitzi, David B.; Blum, Volker; Walsh, Aron (Sustainable energy & fuels, 2017)
To build on the success of other mineral systems employed in solar cells, including kesterites (Cu 2 ZnSnS 4 ) and herzenbergite (SnS), as well as mineral-inspired systems such as lead halide perovskites (CH 3 NH 3 PbI 3 ), we have searched for photoactive minerals with the additional constraint that a polar crystal structure is adopted. Macroscopic electric fields provide a driving force to separate electrons and holes in semiconductor devices, while spontaneous lattice polarisation in polar semiconductors can facilitate microscopic photo-carrier separation to enhance carrier stability and lifetimes. We identify enargite (Cu 3 AsS 4 ), stephanite (Ag 5 SbS 4 ), and bournonite (CuPbSbS 3 ) as candidate materials and explore their chemical bonding and physical properties using a first-principles quantum mechanical approach.